Interaktivitas Pembelajaran untuk Meningkatkan Hasil Belajar IPA Kelas IV Sekolah Dasar - Harya Sandika; Josephirra Josephirra; Yadi Heryadi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study is motivated by the low learning outcomes of students in science subjects, particularly in the topic of energy transformation in fourth-grade elementary school. The lack of student engagement during conventional teaching methods is considered a major factor contributing to poor conceptual understanding. Therefore, this research aims to examine the effectiveness of interactive learning in improving students’ academic performance on the topic. A quantitative approach with a descriptive method was employed. The participants were fourth-grade students at a public elementary school, with data collected through learning outcome tests and classroom observation. The results showed that the implementation of interactive learning significantly enhanced student participation, clarified the concept of energy transformation, and promoted deeper understanding. Students’ average test scores demonstrated a notable improvement after the interactive learning approach was applied. These findings suggest that actively engaging students in the learning process can serve as an effective strategy to address low academic performance in specific science topics. The implications highlight the importance for teachers to adopt more varied and engaging teaching methods to improve the quality of elementary science education.